Evaluating the implementation of a community engaged telehealth based intervention to improve health equity for the unhoused - Johnson, Emily; Marrison, Sarah Tucker; Banks, Mattie; Swords Adams, Cristin (Frontiers in Public Health, 2025)
Unhoused individuals experience numerous barriers to healthcare access and higher morbidity and mortality rates than housed individuals. In collaboration with community-based organizations (CBOs) and healthcare profession learners we developed a program involving in-person and telehealth visits at a CBO clinic and via street medicine outreach to address healthcare needs of the unhoused in a small Southeastern city. In its fifth year of operation, from January through April 2024, we evaluated the program using key stakeholder interviews (patients, CBO staff learners) guided by the Reach Effectiveness Adoption Implementation Maintenance (RE-AIM) framework. A template analysis approach was utilized to evaluate barriers and facilitators to implementation outcomes. Results demonstrated consistent themes across stakeholders. Factors central to reach included advertisement by word-of-mouth, location convenience, and perceived service benefits. For learners, barriers to reach included clinic hours conflicting with academic schedules and apprehension of providing medical care in this setting. Regarding effectiveness, facilitating themes included opportunities for autonomy and enhanced understanding of treatment of underserved populations (learners) and improvement in health (patients, CBO staff). There were no consistently identified unintended negative consequences of the program. For adoption, all stakeholders described strong perceptions of trust in providers and the importance of team communication and coordination of care, in addition to the need to add disciplines included in the multidisciplinary care team. Facilitating implementation themes included comprehensive access for existing patients, while barriers identified were adequacy of access to social resources (housing, food, transportation) and continued increase in numbers of unhoused individuals outpacing available services. Themes facilitating maintenance included continued outreach efforts and integration into existing healthcare and community-based systems. The addition of additional services and specialties was consistently identified as essential to health status of the patients and an opportunity for growth of the program. This implementation evaluation involving key stakeholders of a community engaged telehealth-based intervention for the unhoused provides thematic considerations to guide program implementation and sustainability to improve health equity for vulnerable populations.